2021
DOI: 10.1097/j.pain.0000000000002474
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of grimace scales for pain assessment in nonhuman mammals: a systematic review

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 101 publications
(255 reference statements)
1
39
1
Order By: Relevance
“…Our findings with grimace scales being among the more frequently used are in line with recent reviews stating that facial expressions are widely used as a pain assessment parameter in laboratory rodents ( 41 , 46 ). In this context, it needs to be emphasized that the analysis of the countries of origin of the first author indicated that we are far from a widespread global application of the parameters of interest.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings with grimace scales being among the more frequently used are in line with recent reviews stating that facial expressions are widely used as a pain assessment parameter in laboratory rodents ( 41 , 46 ). In this context, it needs to be emphasized that the analysis of the countries of origin of the first author indicated that we are far from a widespread global application of the parameters of interest.…”
Section: Discussionsupporting
confidence: 91%
“…A scoping review by Whittaker et al examined the MGS in different types of pain (e.g., visceral pain after injection of Freund's adjuvant), indicating a wide application of the MGS in different animal models ( 45 ). A recent scoping review focusing on the grimace scales in non-human mammals has already intensely studied the level of evidence for measurement properties of various grimace scales reporting a high level of evidence for MGS and RGS ( 46 ). Our analysis is more specifically focused on the application of post-operative pain induced by different types of surgeries under general anesthesia in mice and rats, including the extraction of information about anesthesia and perioperative analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in rodent experiments, there are surprisingly few reports measuring pain or nociception in experimental rabbit models, even those modeling knee osteoarthritis or intervertebral disc dislocation (Lei et al, 2017; Mans, 2020; Yoshioka et al, 1996). Composite pain scales for rabbits in a clinical environment (Banchi et al, 2020) and the Bristol Rabbit Pain Scale (Benato et al, 2021) examine and score rabbit facial expressions and other behaviors to assess pain, such as the grimace scale (Evangelista et al, 2021; Keating et al, 2012). Yet, recent reports suggest that the experimenter's presence can have a profound effect on the animal's behavior and subsequent score on these tests (Pinho et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in rodent experiments, there are surprisingly few reports measuring pain or nociception in experimental rabbit models, even those modeling knee osteoarthritis or intervertebral disc dislocation (Lei et al, 2017; Mans, 2020; Yoshioka et al, 1996). Composite pain scales for rabbits in a clinical environment (Banchi et al, 2020) and the Bristol Rabbit Pain Scale (Benato et al, 2021) examine and score rabbit facial expressions and other behaviors to assess pain, such as the grimace scale (Evangelista et al, 2021; Keating et al, 2012). Yet, recent reports suggest that the experimenter’s presence can have a profound effect on the animal’s behavior and subsequent score on these tests (Pinho et al, 2020).…”
Section: Discussionmentioning
confidence: 99%